Non-contact injury incidence in professional women’s football depends on the starting status of the player - Moreno-Perez, Victor; Bové, Berta Carles; Courel-Ibáñez, Javier; Coso, Juan; Beato, Marco; Vidal-Barraquer, Eva Ferrer; Font, Gil Rodas (Biology of Sport, 2025)
This study aimed to determine differences in the incidence of non-contact injury in professional women football players with different starting statuses. Data from 37 women (age: 28.5±3.9 years; body mass: 62.3±5.2 kg; height: 169.8±4.7 cm) from a professional football team (Professional Women’s Football League from Spain) were prospectively collected during two consecutive seasons. Players were classified according to their match starting status as starters (players with > 70% of matches in the starting lineup; n = 20) and non-starters ( n = 17). External load parameters were collected using GPS in all training sessions and matches. Non-contact injuries were diagnosed, classified, and recorded by the medical staff following the IOC consensus. Statistics included comparisons of starters vs. non-starters and linear regression and diagnostic analyses of injured vs. non-injured players. Non-starters accumulated less match load over the season but had two-fold non-contact injury incidence and three-fold muscular injury incidence during matches than starters, despite being exposed to a similar training load. The larger the number of matches played as a starter, the fewer injuries (non-contact: R 2 = 0.27, p = 0.01; muscular: R 2 = 0.11, p = 0.04). Diagnostic analyses identified clinical thresholds for insufficient match and training loads during the season accounting for higher injury risk. Less than 5,237 decelerations and 25 matches as a starter per season during training was the best indicator to discriminate players with less likelihood of non-contact injury. Football players with less match exposure from a women’s professional squad may be more prone to injury due to under-exposure to the demands of the game.